Atitudes dos profissionais da rede socioeducativa frente ao álcool, alcoolismo e alcoolista - Gonçalves, Wanderson dos Santos (2014)
The world consumption of alcohol has increased significantly in recent decades, a phenomenon that has contributed to the increased burden of disease worldwide. The qualification of the professionals who deal with the drug user population is of great concern. In this context, the creation of Regional Centres of Reference (CRR) for ongoing training is required. Therefore, this study aims to identify the perception of the professional who deals daily with this problem related to alcohol, alcoholism and alcoholics before and after their participation in a training course. An exploratory, descriptive study of comparative quasi-experimental approach, whose research is based on the measurement of the attitudes of a group of professional participants of the course offered by the Regional Reference Center on Drugs of the Holy Spirit (CRR-ES) was performed. Scale of Attitudes towards alcohol, alcoholics and alcoholism created and validated by Vargas (2005), applied in the pre and post training was used as a tool. And, the final sample consisted of 131 participants, 53 psychologists, 51 social workers, 20 nurses, 2 and 6 with lawyers profession not specified. Professionals tended to have more positive attitudes towards alcohol, alcoholism and alcoholics after participating in the training. The major predictors of positive attitudes were found in this study have experience to work with this clientele and have participated in this training. Porting, it was shown that the level of knowledge directly influences the attitudes of the professional front towards alcohol, alcoholics and alcoholism, and the greater the greater knowledge tend to have more positive attitudes.